Contribution of native arbuscular mycorrhizal fungi in the stablishment of Aristida setifolia Kunth in degraded areas in the cerrado - Martins, Carlos Romero; de Miranda, Jeanne Chistine Claessen; de Miranda, Leo Nobre (Pesquisa Agropecuaria Brasileira, 1999)
To study the dynamics of native AM fungi, in natural cerrado soil and three degraded areas, quantitative and qualitative avaliations were done, in the dry and rainy seasons. Those avaliations included field experiment plots from a degraded area with lime, natural peat and castor bean cake. Two greenhouse experiments studied the contribution of AM fungi to the stablishment of a spontaneous grass Aristida setifolia Kunth. The first used natural and steam sterilized substrates from the four areas; the second, field plots substrates steam sterilized with and without inoculation of three native AM fungi. In the field, soil density was higher in degraded areas and both areas presented high soil acidity. The AM fungi were present in all areas with higher number of spores and species in the rainy season. In the greenhouse experiments, native AM fungi promoted a significant increase in plant shoot dry matter. In the noninoculated field plots substrates, there was no significant effect of lime and organic compounds on plant growth. However, with the inoculation, there was a significant increase in grass shoot dry matter, with a significant improvement and differentiation of the field treatments effects.